2021
DOI: 10.18488/journal.1.2021.111.56.64
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of Social Assets Condition among Urban Farmers of the Community Garden in Klang Valley, Malaysia

Abstract: Social assets Urban farmers Urban agriculture Community garden. Social assets have been focus of interest in considerable social science academic circles in recent years. Development of community garden is needed in order to provide a wellbeing among urban communities through utilizing their social assets in terms of togetherness and relationship concerns. It's seen as the motivational and adhesive forces for communitarian work that benefit in agriculture development in urban areas. However, previous studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Along with the results of the FGDs, urban poor children perceived some barriers for them to do the gardening. Similar to previous findings by Zainal and Rosmiza (2021), children's busy schooling schedule is one of the main barriers for them to be involved in gardening activity. Therefore, this factor should be taken into consideration in planning of intervention schedule.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Along with the results of the FGDs, urban poor children perceived some barriers for them to do the gardening. Similar to previous findings by Zainal and Rosmiza (2021), children's busy schooling schedule is one of the main barriers for them to be involved in gardening activity. Therefore, this factor should be taken into consideration in planning of intervention schedule.…”
Section: Discussionsupporting
confidence: 87%
“…Home-based gardening programmes are likely to improve home food availability (Galhena et al, 2013), particularly fresh produces such as vegetables and fruits, strengthening family relationships, promote healthy eating and active lifestyles (Eigenbrod & Gruda, 2014;Ornelas et al, 2017). However, previous study had reported a lack of involvement or participation of gardening in home garden among the Malaysian urban poor children (Zainal & Rosmiza, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies test the contribution of urban gardening to the preservation of natural ecosystems ( [116,117]) and the sustainability of agricultural systems (see, e.g., [118]), and to food self-sufficiency and security ( [3]). Others focus on the diffusion of social assets among urban farmers and community gardens [119], the possible relations between cultivation and better consumption choices and stress reduction ( [120,121]), and social relationship improvement [122].…”
Section: Results Motivationsmentioning
confidence: 99%
“…In contrast, Dorn et al (2021) [125], Hencelova et al (2021) [122] and Feinberg et al (2021) [112] claim that there is no confirmation of such motivations. Turner (2020) [105] and Zainal (2021) [119] include motivations that Cattivelli ignores, such as those related to the rationalisation of the agri-food system (sharing of knowledge, transfer of technology, and the adoption of sustainable agricultural practises).…”
Section: Results Motivationsmentioning
confidence: 99%